Synthesis of octahedron Zn2SnO4 by hydrothermal method for high performance ethanol sensor - Hanh, Nguyen Hong; Duy, Lai Van; Hung, Chu Manh; Duy, Nguyen Van; Hieu, Nguyen Van; Hoa, Nguyen Duc (Vietnam Journal of Science and Technology, 2020)
The octahedron Zn2SnO4 was prepared through a facile hydrothermal method for ethanol gas-sensing application. The synthesized material was characterized by scanning electron microscopy (SEM), powder x-ray diffraction (XRD). The gas-sensing characteristics were measured at various concentrations of ethanol at temperature ranging from 350 to 450 ºC. The gas response exhibits good linear relationship with the increasing of ethanol concentrations in the range of 50-250 ppm. Gas-sensing measurements demonstrated that the synthesized octahedron Zn2SnO4 showed n-type semiconducting behavior, where the sensor resistance decreased upon exposure to ethanol. Results pointed out that the sensors showed the highest response value at operating temperature of 400 ºC. The sensor response value was 30 at 250 ppm ethanol.  Such outstanding gas sensing property might be attributed to the morphology of the octahedra which provided large contact area between Zn2SnO4 and target gas. The synthesized octahedron Zn2SnO4 is potential for detecting traces of ethanol.